Analysis of The Effectiveness of Organic Fertilizer in Improving The Quality And Yield of Cucumber Crops - Nisiyari Halawa; Arni Lestari Waruwu; Feberkat Abdi Mosinema Waruwu; Elman kasih Saputra Gulo; Natalia Kristiani Lase (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study examines the effectiveness of organic fertilizers in improving the quality and yield of cucumber (Cucumis sativus L.) plants through a comprehensive literature study. A systematic review was conducted on recent scientific publications that discuss various types of organic fertilizers, including chicken manure, bokashi, organic liquid fertilizer, and eco-enzyme. The research method used a literature study approach by analyzing articles from 2020-2024, focusing on the effectiveness of organic fertilizers in increasing the growth and productivity of cucumber plants.The results showed that organic fertilizers do not merely provide nutrients, but transform as agents of soil ecosystem regeneration. Each type of organic fertilizer has a unique mechanism in influencing plant growth, including increased microbiological activity, optimization of soil structure, and stimulation of the root system. Variations in plant responses depend on genotype, fertilizer composition and environmental conditions. The research resulted in practical recommendations for sustainable organic fertilization strategies, emphasizing the importance of a precision and holistic approach in cucumber crop nutrient management. The findings make a significant contribution in the development of sustainable agriculture.